2017
DOI: 10.1007/s11060-017-2557-y
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study on the use of cerebrospinal fluid cell-free DNA in intramedullary spinal ependymoma

Abstract: Cerebrospinal fluid (CSF) represents a promising source of cell-free DNA (cfDNA) for tumors of the central nervous system. A CSF-based liquid biopsy may obviate the need for riskier tissue biopsies and serve as a means for monitoring tumor recurrence or response to therapy. Spinal ependymomas most commonly occur in adults, and aggressive resection must be delicately balanced with the risk of injury to adjacent normal tissue. In patients with subtotal resection, recurrence commonly occurs. A CSF-based liquid bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…The promoting effect of DNA on tau aggregation was observed in a wide range from 10 to 1000 ng. The use of these concentrations were informed by the range of cerebrospinal fluid DNA concentrations observed in patients with different diseases: 1 – 600 ng/mL [48-50]. The sources of bacterial and fungal DNA were selected based on the literature and personal data that showed associations of certain microorganisms with AD.…”
Section: Discussionmentioning
confidence: 99%
“…The promoting effect of DNA on tau aggregation was observed in a wide range from 10 to 1000 ng. The use of these concentrations were informed by the range of cerebrospinal fluid DNA concentrations observed in patients with different diseases: 1 – 600 ng/mL [48-50]. The sources of bacterial and fungal DNA were selected based on the literature and personal data that showed associations of certain microorganisms with AD.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have, in the past, demonstrated that a CSFbased liquid biopsy may not be feasible in genetically diverse, anatomically sequestered, and low-grade CNS tumors. 4,7,10,30 The most important factor that is associated with CSF-ctDNA levels is anatomical sequestration. Jimenez et al described three CNS barriersthe BBB, the blood-CSF barrier of the choroid plexus and arachnoid membrane, and the CSF-parenchyma barrier of the ependymalas potentially usable for tumor studies.…”
Section: Anatomical Constraints Of Cns Tumorsmentioning
confidence: 99%
“…31 In cases where parenchyma or arachnoid membranes surround a tumor, the diffusive ability of tumor-derived DNA to diffuse into the CSF could be limited significantly due to the presence of the blood-CSF barrier and the CSFparenchyma barrier. 4,10,30 Connolly et al 30 encapsulated entirely by the brain or spinal cord parenchyma. Interestingly, all four low-grade gliomas directly adjacent to the CSF reservoir did not have reliably detectable ctDNA.…”
Section: Anatomical Constraints Of Cns Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Connolly et al . analysed CSF and blood samples of three cases of grade II intramedullary ependymomas without identifying any alteration in blood or in CSF . In this regard, other variables such as CSF flow alterations may affect cfDNA circulation and liquid biopsy sensitivity.…”
Section: Circulating Cell‐free Nucleic Acids Analysismentioning
confidence: 99%